A REVIEW ON SESAME - AN ETHNO MEDICINALLY SIGNIFICANT OIL CROP: Life Sciences-Botany - NAGPURKAR MUKTA,; PATIL NEETA M, (International Journal of Life Science and Pharma Research, 2022)
Herbal medicines are popular in the treatment of many diseases. They are safe and easily available. India produces different oil seeds like groundnut, mustard, rapeseed and sesame seed and substantial quantity of edible oils is consumed here. Sesame is widely known oil crop of Pedaliaceae family with bell shaped purple or white coloured flowers. The fruits of the plant are oblong capsules containing numerous small and oval seeds which show colours like white, red, brown or black. Sesame seeds were thought to have first originated in India and are also mentioned in early Hindu legends. Sesame seeds, oil and other parts of plant have numerous uses from preparations of hair oils to treatments of various ailments in human as well as in cattle. An ethno-botanical review of sesame provides information about therapeutic use of sesame seeds and even other parts of plant for different ailments.